1993
DOI: 10.1007/bf00588720
|View full text |Cite
|
Sign up to set email alerts
|

MRI appearances of an ectopic pituitary adenoma: case report and review of the literature

Abstract: MR images of an ectopic pituitary adenoma have been published in only a single case, a suprasellar mass. We present a patient with Cushing's disease in whom MRI revealed a pituitary adenoma within the sphenoid sinus. Radiologic characteristics of ectopic pituitary adenomas are reviewed, with emphasis on MRI, which demonstrates a soft tissue mass, isointense with gray matter on T1-weighted images, which enhances in a heterogeneous manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 19 publications
0
25
1
Order By: Relevance
“…The solid areas of EPAs show strong enhancement and, when juxtaposed with the relatively low signal intensity of secretion-filled spaces, result in a characteristic cribriform pattern, which may be an important suggestive sign. Sphenoid sinus EPAs with relatively large cyst formation, necrosis, haemorrhage or proteinaceous secretions were reported to be seldom seen [1][2][3][4]. However, three cases with cysts were identified in the present series.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…The solid areas of EPAs show strong enhancement and, when juxtaposed with the relatively low signal intensity of secretion-filled spaces, result in a characteristic cribriform pattern, which may be an important suggestive sign. Sphenoid sinus EPAs with relatively large cyst formation, necrosis, haemorrhage or proteinaceous secretions were reported to be seldom seen [1][2][3][4]. However, three cases with cysts were identified in the present series.…”
Section: Discussioncontrasting
confidence: 47%
“…A review of the English literature has shown, to date, fewer than 40 cases [1][2][3][4][5][6]. Furthermore, some authors think a pre-operative diagnosis of EPA is often difficult to make.…”
mentioning
confidence: 99%
“…Regarding Cushing's disease due to corticotropinomas, the ratio of circulating ACTH (pg/ml by IRMA) to cortisol (mg/dl) was found to be 2.4 to 2.6 or 5.1 to 5.5 in cases of microadenoma or macroadenoma, respectively [30]. Based on this finding, the present case [7.25 to 12.1] and the other three [8.08, 12.0 and 8.0] out of 16 EAPA cases documented (see Table 1) were shown to have relatively high ratios of ACTH (pg/ml) to cortisol (mg/dl) com- pared to common Cushing's diseases, although these three cases, unlike our case, were reported to have completely overt Cushingoid features including moon face, truncal obesity, skin striae, pigmentation and atrophy, cervicodorsal hump, hypertension and diabetes mellitus [4,13,15]. Although the discrepancy of clinical symptoms and endocrine profile could be related to the individual sensitivity to cortisol, it is also possible that an aberrant less-active ACTH molecule exists in the plasma of these EAPA patients [31].…”
Section: Discussionmentioning
confidence: 52%
“…1A and B). On her endocrine examinations, plasma ACTH level was markedly increased (196 to 280 pg/ml; normal, 9-52) but the serum cortisol level was not remarkable (23 to 27 mg/dl; normal [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Daily secretion of ACTH and cortisol lacked the normal circadian rhythm (Fig.…”
Section: Case Reportmentioning
confidence: 99%
“…Intracranial and extracranial locations are known, 4,6,[10][11][12][13][14][15][16][17][18][19][21][22][23] most often in the suprasellar region 6,12,13,15,16) or the sphenoid sinus. 4,6,10,14,22) Only four of 65 (6.2%) reported ectopic pituitary adenomas have been found in the cavernous sinus. 6) We present a case of adrenocorticotropic hormone (ACTH)-positive ectopic pituitary adenoma in the cavernous sinus manifested as sudden onset of oculomotor nerve paresis and did not cause Cushing's syndrome.…”
Section: Introductionmentioning
confidence: 99%